Risk factors associated with non-communicable diseases among government employees in Nepal: insights from a cross-sectional study - Durga Datta Chapagain; Durga Datta Chapagain; Kennedy Mensah Osei; Danik Iga Prasiska; Heejin Kimm; Vasuki Rajaguru; Sunjoo Kang; Tae Hyun Kim; Sang Gyu Lee; Whiejong Han (Frontiers in Public Health)
IntroductionSedentary lifestyles, unhealthy work environments and occupational stress increase the risk of Non-Communicable Diseases (NCDs) among government employees, impacting healthcare costs and productivity. This study aimed to investigate the prevalence of hypertension, prediabetes, and diabetes, and identify risk factors among government employees in Nepal.MethodsA cross-sectional study was conducted among 994 government employees. Data on sociodemographic, anthropometric/biochemical measurements, behavioral and clinical factors were collected. Descriptive analysis analyzed the prevalence of NCDs among covariates. Multivariate logistic regression and ROC curves assessed the association between NCDs and covariates/risk factors. Significance was set at p < 0.05 and 95% CI.ResultsParticipants’ mean age was 33.1 ± 9.1 years, with 82.1% (n = 796) male, mostly from aged 30–39 (n = 397, 41%), and Brahmin/Chhetri (n = 454, 46.9%). Elders had a 6-times higher risk of hypertension (OR: 6.08, CI: 3.1–11.92), above 7-times higher risk of prediabetes (OR: 7.83, CI: 3.32–18.47), and above 16 times higher risk of diabetes (OR: 16.62, CI: 2.5–106.49) compared to aged 18–29. Smoking increased diabetes-risk (OR: 6.82 CI: 1.95–23.8), while alcohol-consumption increased risk of hypertension (OR: 1.51, CI: 1.02–1.63) and prediabetes (OR: 1.88, CI: 1.08–3.28). Overweight increased hypertension risk (OR: 2.79, CI: 1.90–4.09), while obesity increased both hypertension (OR: 3.04, CI: 1.73–5.34) and prediabetes-risk (OR: 2.43, CI: 1.18–4.99).ConclusionThis study recommends concerned authorities to implement workplace policies for health promotion, intensify awareness campaigns, establish routine screening for government employees, and focus on reducing risk factors and encouraging healthier lifestyles to enhance NCDs prevention.